Surgical outcomes of proximal femoral bone cysts in pediatric patients: a retrospective study of 41 cases - Li, Taichun; Dai, Zhenzhen; Ma, Qichao; Zhou, Han; Li, Hai; Zhang, Ziming (Frontiers in Pediatrics, 2024)
The aim of this study was to evaluate the surgical outcomes of proximal femoral bone cysts in pediatric patients.We retrospectively analyzed 41 pediatric patients (31 males and 10 females, mean age 7.47 ± 2.67 years, range 2.03-14.67 years) diagnosed with proximal femoral bone cysts treated at a single institutetreated at the Xinhua Hospital, affiliated with the Shanghai Jiao Tong University School of Medicine, between March 2009 and November 2021. Data included demographics, preoperative details, intraoperative conditions, surgical techniques, postoperative outcomes, recurrence, and complications.Results: Of the participants, 68% presented with simple bone cysts and 32% with aneurysmal bone cysts. Prior to surgery, 32% exhibited pathological fractures. Surgical methods included lesion curettage, defect filling using allograft bone and Minimally-Invasive Injectable Graft X3, and varied fixation techniques. Postoperative recurrence (17%) was associated with cyst location between the capital femoral epiphysis and the linea intertrochanterica (P = 0.010). At the final assessment (mean follow-up: 26.51 ± 18.99 months), all showed radiological bony union with 93% rated as 'good' and 7% as 'fair' based on Ratliff hip scores. Complications arose in 20% of patients, significantly correlated with prior pathological fractures( P = 0.007) and their association with the linea intertrochanterica( P = 0.004). Those with fractures reported higher intraoperative blood loss(P = 0.015) and longer surgery durations(P = 0.012) compared to those without.Treating pediatric proximal femoral bone cysts using techniques such as lesion curettage, defect filling, and selective internal fixation yields favorable outcomes. The presence of pathological fractures can prolong surgical time, increase intraoperative blood loss, and elevate postoperative complication risks. Hence, early surgical intervention for these cysts is recommended to prevent fractures.